Screening and socioeconomic associations of dyslipidemia in young adults - Stephen E. Hudson; Matthew S. Feigenbaum; Nirav Patil; Elan Ding; Alex Ewing; Jennifer L. Trilk (BMC, 2020)
Abstract Background The Southern region of the United States is home to substantial populations with obesity, dyslipidemia, and hypertriglyceridemia, while also housing a large percentage of America's minority, rural, and low socioeconomic status (SES) peoples. Adult-onset cardiovascular disease (CVD) research may be informed by investigating associations(s) between late adolescent demographic variables and lipid values. Our objective was to investigate lipid parameter associations with college-age socioeconomic status, which may improve age-specific screening algorithms for management or prevention of adult-onset CVD. Methods Using an Analysis of Variance test and a general linear model, associations between gender, race/ethnicity, SES, and athletic participation on lipid parameters (VLDL-C, LDL-C, TG, TC, and HDL-C) were analyzed in 4423 private liberal arts college students enrolled in freshman-level wellness courses at Furman University in Greenville, SC. Comparative data were collected from an age-matched sample (National Health and Nutrition Examination Survey: NHANES 2003-2016). Our main outcomes were statistically significant relationships between any lipid values (TC, HDL-C, LDL-C, TG) and any demographic variables (gender, SES, ethnicity, athlete status). Results Males demonstrated lower TC and LDL-C, and higher HDL-C values. HDL-C was highest in athletes. African-American students demonstrated healthier VLDL-C, TG, and HDL-C values. With similar distributions, the age-matched NHANES comparison group showed unhealthier values in nearly all categories. Conclusions College students may have better lipid health than the general population. African-Americans may have seemingly healthier lipid values than age-matched individuals independent of athletic or college enrollment which has already been demonstrated in other studies. Future research should include SES relationships in lipid screening paradigms along with other appropriate risk factors for cardiovascular disease. Based on our comparative data, pediatric health providers and researchers may consider education as a potential protective factor against poor lipid health when considering lipid screening protocols for students.